GAGASAN PENGADUAN KONSTITUSIONAL DALAM KONSEPSI NEGARA KESEJAHTERAAN DI INDONESIA - Yuwanto, Yuwanto (Faculty of Social and Political Sciences Diponegoro University)
Abstract:Â The constitutional complaint represents an instrument for the protection of the individual rights of citizens. Acting on a constitutional complaint as a specific positive-procedural instrument for protection of constitutionally guaranteed citizen rights and freedoms of citizens is becoming a more and more acceptable and applicable instrument. Indonesian Constitutional Court is one of the judicial organs with special jurisdiction as stipulated in the Constitution. This institution is able to introduce a new legal culture based on the rule of law principles. Based on the assumption that constitutional complaint is an important part of the welfare state concept, our Constitutional Court can plays a pivotal role to materialize those individual citizen basic rights.Keywords: welfare state, individual basic rights, constitutional complaint.permalink:Â http://ejournal.undip.ac.id/index.php/forum/article/view/3200